2013
DOI: 10.1007/s11103-013-0047-y
|View full text |Cite
|
Sign up to set email alerts
|

In-depth proteome analysis of the rubber particle of Hevea brasiliensis (para rubber tree)

Abstract: The rubber particle is a special organelle in which natural rubber is synthesised and stored in the laticifers of Hevea brasiliensis. To better understand the biological functions of rubber particles and to identify the candidate rubber biosynthesis-related proteins, a comprehensive proteome analysis was performed on H. brasiliensis rubber particles using shotgun tandem mass spectrometry profiling approaches-resulting in a thorough report on the rubber particle proteins. A total of 186 rubber particle proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 58 publications
3
54
1
Order By: Relevance
“…A recent study identified 186 rubber particle proteins [25], but latex contains far more proteins, from which at least 15 have been internationally assigned as allergens named Hev b 1-15 (Table 2; [111,112]). REF and SRPP are recognized as major allergens found in latex [29,37,71,102,110].…”
Section: Allergenicity: a Side Effect?mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study identified 186 rubber particle proteins [25], but latex contains far more proteins, from which at least 15 have been internationally assigned as allergens named Hev b 1-15 (Table 2; [111,112]). REF and SRPP are recognized as major allergens found in latex [29,37,71,102,110].…”
Section: Allergenicity: a Side Effect?mentioning
confidence: 99%
“…A proteome analysis revealed the presence of more than 1300 protein spots in latex and nearly 600 in rubber particles [24]. In 2013, Dai et al identified 186 different proteins in rubber particles [25]. As seen on a polyacrylamide gel electrophoresis stained by Coomassie Blue (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The rubber particle of H. brasiliensis contains at least 186 proteins based on proteomic analysis [27], while the whole cytoplasm latex of H. brasiliensis contains over 300 proteins [24], including 15 that have been identified thus far as being clinically significant in human type I latex allergy. These 15 proteins represent the canonical Hevea allergens, named Hev b 1 through Hev b 15 by the World Health Organization International Union of Immunological Studies (IUIS) (http://www.…”
Section: Discussionmentioning
confidence: 99%
“…The draft genome sequence of H. brasiliensis was achieved in 2013, identifying 16 Hev b 6 genes [14]. The presence of hevein isoforms has been shown by several studies at all levels of expression (genes, mRNA and proteins).…”
Section: Genes and Variantsmentioning
confidence: 99%
“…To date, 1,499 proteins have been found in latex [12,13]. At least 186 proteins have been reported to be present on rubber particles [14] and 169 have been extracted from lutoids and the bottom fractions [15]. Hevein belongs to the lutoid proteins and represents approximately 20% of the dry matter of the bottom fractions [16,17].…”
Section: Introductionmentioning
confidence: 99%